NEW IDEAS TO ULTRASOUND DIAGNOSTICS OF EMBOLOGENIC VENOUS THROMBOSIS - I. M. Goldina (Неотложная медицинская помощь, 2016)
ABSTRACT. The development of new ideas to the ultrasound diagnostics of embologenic venous thrombosis on base of the collection of anatomical and structural functional ultrasound criteria of embologenic venous thrombus is discussed.The investigations of 780 patients (800 lower limbs) were included in the current work. The presence of floating thrombi did not finish into PE (55,4% (302/545) cases). The analysis of frequency distribution of floating thrombi (n=545) in addition embologenic floating thrombi (n=302) in of inverior vein cava and comparative evaluation of unembologenic (n=243) and embologenic (n=302) floating thrombi from the form, the contour, structure of the thrombus and the counter, the mobility of the thrombus. The analysis of absolute and relative errors of the measuring of the length of the floating thrombus of iliac-femoral segment showed that the length of the floating thrombus is not reliable criterion of embologenic thrombus (n=177).Ultrasound criteria of the embologenic floating thrombus and thrombi with fragmented surface were found. The detection of embologenic floating thrombi decreases the value of implanted cava-filters and thrombectomies.